2023
DOI: 10.1002/cjoc.202200761
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Branched Block Copolymer Assemblies via RAFT Dispersion Polymerization Using Branched Macro‐RAFT Agents

Abstract: Here, we demonstrate the use of branched macromolecular reversible addition-fragmentation chain transfer (macro-RAFT) agents in RAFT dispersion polymerization, to access branched block copolymers as well as well-defined branched block copolymer assemblies. Two types of branched macro-RAFT agents were first synthesized by using either a monofunctional chain transfer monomer or a difunctional chain transfer monomer in RAFT polymerization, and subsequently utilized in RAFT dispersion polymerization. It was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…This additional compartmentalization opens up possibilities for co‐delivery of two different cargo types. Moreover, branched polymer structures can be included in the NP design 190 . Although more challenging to reproduce and characterize, branching offers an additional handle of control, for example, by promoting morphological transitions at lower DPs compared to linear BCPs 191,192 …”
Section: Advances Of Pisa For Potential Future Ddsmentioning
confidence: 99%
“…This additional compartmentalization opens up possibilities for co‐delivery of two different cargo types. Moreover, branched polymer structures can be included in the NP design 190 . Although more challenging to reproduce and characterize, branching offers an additional handle of control, for example, by promoting morphological transitions at lower DPs compared to linear BCPs 191,192 …”
Section: Advances Of Pisa For Potential Future Ddsmentioning
confidence: 99%
“…Over the past decade, RAFT–PISA has emerged as a powerful technique to prepare various block copolymer nanoparticles with high solids content (10–50%). 18–34 Moreover, RAFT–PISA is also a useful synthetic tool for the synthesis of well-defined polymers with low dispersities. 35–39 However, recent progress in controlling dispersities of polymers has shown that dispersity is also an important parameter that is used to tune properties of polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…This method has shown great success in producing highly uniform polymeric microspheres with tailor-made surface functionality by utilizing different functional macro-RAFT agents. It should be mentioned that this method is different from the well-studied RAFT dispersion polymerization-induced self-assembly (PISA) that forms well-defined block copolymers and block copolymer nanoparticles. In a typical PISA formulation, a macro-RAFT agent with good RAFT control over monomers should be used. Despite the advantages of photoinitiated RAFT dispersion polymerization, there are still some limitations to this approach due to the use of photoinitiation.…”
Section: Introductionmentioning
confidence: 99%